Radiation and criticality safety analyses for the highly-enriched uranium core removal from a research reactor. (November 2017) - Dennis, Haile; Grant, Charles; Preston, John
Abstract: Analysis was performed to estimate radiation levels during removal and packaging of the highly-enriched uranium core of the JM-1 SLOWPOKE-2 research reactor. Due to severe limitations of space in and around the reactor pool, the core could not be removed in the conventional manner as was done for previous SLOWPOKE defuelling operations. A transfer shield, with a balance between shielding efficacy, volume and weight was designed. Fuel depletion, Monte Carlo shielding and criticality calculations were performed. Comparisons of measured and calculated dose rates as well as results of the criticality safety assessment are presented. The designed transfer shield reduced the calculated unshielded dose rate from 29 Sv/h to 8 mSv/h. The maximum calculated effective neutron multiplication factor of approximately 0.89 was below the 0.91 upper subricital limit. Highlights: A transfer shield was designed to remove the highly-enriched uranium core from a research reactor. Calculations were performed to determine the core's fission product inventory and radioactivity. Transfer shield reduced dose rates from 29 Sv/h to 8 mSv/h. Maximum individual dose was 0.84 mSv. Criticality analysis showed that the core was sufficiently subcritical in all situations.